Pre-renal chronic kidney disease in a domestic cat presenting with FLUTD-like symptoms - Jasmine Yasyfa' Sukmayani; Aliffa Pinquita Sabrina; Maharani Wisesa Vidya Tresna; Pranyata Tangguh Waskita (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2025)
Chronic kidney disease (CKD) is a progressive condition in aging cats that often presents with signs of overlapping feline lower urinary tract disease (FLUTD). Early recognition and differentiation are crucial for its management and prognosis. This case study discusses a 5-year-old cat with CKD who initially showed FLUTD-like symptoms, including three days of anuria, dehydration, and anorexia. Diagnostics, including examination, ultrasonography, urinalysis, hematology, and serum biochemistry, revealed elevated creatinine, amylase, and BUN levels, indicating pre-renal impairment and decreased GFR. Treatment involved cystocentesis, hepacartine, azody, ippakitine, vitamin B-complex, and a renal-support diet (Royal Canin Renal Wet Food). After two weeks, the cat showed clinical improvement with clear urine and normalized biochemistry.